Exploring Cooperative Learning for Keyboarding Proficiency: A Case Study of Polytechnic Students in Southwest, Nigeria - Bolarinwa, Fehintola Fatimoh Bintu; Lasun Gbadamosi; Taiwo Edun (PERSPEKTIF, 2024)
Effective keyboarding skills are essential for success in office management roles. However, concerns remain about the declining practical mastery of keyboarding among Office Technology and Management (OTM) students in polytechnics in Southwest Nigeria. This study examines the effectiveness of cooperative learning strategies in addressing this issue. Using a quasi-experimental design with a 3x2x2 factorial matrix, 325 ND I OTM students were exposed to three instructional strategies (cooperative learning, gamification, and conventional demonstration), with two moderating variables (gender and locus of control). The results reveal a significant effect of the instructional strategy on keyboarding achievement (F(2,225) = 48.731, p < 0.05), with cooperative learning demonstrating notable effectiveness. Neither gender (F(1,209) = 0.986, p > 0.05) nor locus of control (F(2,255) = 0.426, p > 0.05) showed a significant impact on achievement. These findings suggest that integrating cooperative learning strategies with conventional methods can enhance the keyboarding skills of OTM students, contributing to their overall growth in office technology and management.